1995
DOI: 10.1074/jbc.270.37.21869
|View full text |Cite
|
Sign up to set email alerts
|

Glu-96 of Basic Fibroblast Growth Factor Is Essential for High Affinity Receptor Binding

Abstract: The importance of basic fibroblast growth factor (bFGF) in several pathophysiological processes has stimulated interest in the design of receptor antagonists to mitigate such effects. Of key importance in this connection is the characterization of the functional binding epitopes of the growth factor for its receptor. Based on peptide mapping and molecular dynamics calculations of the three-dimensional structure of basic fibroblast growth factor, we employed site-directed mutagenesis to investigate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Rat mtFGF contains a substitution of glutamine-104 with an alanine residue, equivalent to the glutamine-96 mutation on human FGF-2. This mutation produces FGF-2 that binds to the lowaffinity HSPG sites with unchanged affinity but has diminished affinity for FGFR1 (50). Our own characterization confirmed that, although mtFGF-2 was retained by the heart (presumably by binding to HSPGs of the basement membrane and the extracellular matrix) and localized around cardiomyocytes (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Rat mtFGF contains a substitution of glutamine-104 with an alanine residue, equivalent to the glutamine-96 mutation on human FGF-2. This mutation produces FGF-2 that binds to the lowaffinity HSPG sites with unchanged affinity but has diminished affinity for FGFR1 (50). Our own characterization confirmed that, although mtFGF-2 was retained by the heart (presumably by binding to HSPGs of the basement membrane and the extracellular matrix) and localized around cardiomyocytes (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…2D) as well as irreversibly injured myocytes that have lost their antivinculin staining. No differences were evident in the staining pattern of wt-or mtFGF-2, as expected from their similar affinity to heparin (50).…”
Section: Resultsmentioning
confidence: 80%
“…In conclusion, the data presented in this report show that FGF4 adopts a typical ␤-trefoil fold similar to other FGFs (24,28,43). A ternary FGF4-FGFR1-heparin model constructed by superimposing FGF4 onto FGF2 in the FGF2-FGFR1-heparin structure assisted the identification of several key residues in FGF4 involved in receptor and heparin binding.…”
Section: Resultsmentioning
confidence: 94%
“…This was particularly unexpected for the E159A mutant, because Glu-159 is highly conserved among FGFs (Fig. 1B) and the corresponding glutamic acid in FGF2 (Glu-96) was shown to be critical for binding of FGF2 to FGFR1 (43).…”
Section: Resultsmentioning
confidence: 99%
“…3. Five of the above seven amino acids (Y24, E96, N101, Y103, and L140) have been implicated to be important for receptor binding on the basis of site-directed mutagenesis studies (33,35). These amino acids form the primary FGFR binding site, as discussed below.…”
Section: Resultsmentioning
confidence: 99%